2005
DOI: 10.1021/jf040467j
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Composition and Sensory Characters of Commercial Galician Orujo Spirits

Abstract: Nineteen samples of commercial Galician orujo spirits were analyzed by gas chromatography and distinguished from one another on the basis of the concentrations of major volatile compounds (methanol, higher alcohols, esters, acetates, and aldehydes). The spirits were also sensorily analyzed to emphasize this differentiation and to establish a sensory profile as a function of the attributes defined by the tasters. The results show that the Galician orujo spirits present notably significant differences in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 9 publications
5
69
0
1
Order By: Relevance
“…Rose flavor, apple blossom flavor and neroli flavor were the main flavors in 77%vol spirit while fruity and floral flavors were obvious in 80%vol spirits. These were similar to the previous studies, in which the floral and fruity flavors were also described as the main aroma characteristics (Diéguez et al, 2005;Zhao et al, 2012).…”
Section: Principal Component Analysis (Pca) Of Volatile Compoundssupporting
confidence: 92%
See 2 more Smart Citations
“…Rose flavor, apple blossom flavor and neroli flavor were the main flavors in 77%vol spirit while fruity and floral flavors were obvious in 80%vol spirits. These were similar to the previous studies, in which the floral and fruity flavors were also described as the main aroma characteristics (Diéguez et al, 2005;Zhao et al, 2012).…”
Section: Principal Component Analysis (Pca) Of Volatile Compoundssupporting
confidence: 92%
“…This is similar to the results from Zhang et al (2007), who reported that acids were the most abundant aromatic compounds in wine. However, Diéguez et al (2005) reported that terpenes (like β-pinene) and volatile alcohols (like citronellol) were intensive for Orujo Spirits. Volatile alcohols were also reported as the primary aroma components for banana spirits (Capobiango et al, 2015), raspberry, strawberry, and mulberry wines (Feng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were delivered by local agricultural distilleries (Pomeranian region). The raw spirits selected for this study (39 samples) differed in organoleptic properties; 13 of them reached the highest rating from sensory analysis performed in accordance with Polish Standard PN-A-79 528-2:2002 (samples 27-39); 13 spirits received diverging ratings during the sensory analysis-some of the evaluating panelists found them to satisfy the standard, some rated otherwise (samples [14][15][16][17][18][19][20][21][22][23][24][25][26]; the remaining 13 samples did not fulfil the organoleptic requirements (samples 1-13). Preliminary sensory analyses of samples were carried out in the laboratory of Sobieski Distillery.…”
Section: Experimental Samples and Chemicalsmentioning
confidence: 99%
“…On the basis of the known literature, nine sensory descriptors were chosen, often used in the analysis of alcoholic beverages: onion/vegetable, earthy/ mouldy, bread/toast, fruity/sweet, chemical/solvent, nauseating, acrid/ penetrating, green/plant and tart. [8][9][10][11][12][13][14][15][16][17][18] A four-point scale of intensity of a given odour was used to evaluate quantitatively the intensity of each of these descriptors: 3 points, very intense odour; 2 points, odour of medium intensity; 1 point, not intense odour; 0 points, no odour. The samples of raw spirits were diluted to 20% ethanol concentration.…”
Section: Sensory Analysismentioning
confidence: 99%